The Influence of Personality on Students' Interpersonal Communication Skills and Intercultural Adaptation: Integration of the Big Five and Berry Acculturation Models: PLS-SEM Analysis - Sulaiman Abdul Rasid; M. Fadli Al Azhari (FKIP UNSULTRA, 2026)
This study examines the influence of personality on interpersonal communication skills and cross-cultural adaptation of students from Sumatra studying in East Java. This phenomenon is important because of differences in communication norms between the two regions that could potentially create adaptation barriers. The study used an ex-post facto cross-sectional design with 85 respondents, analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that interpersonal communication skills significantly influenced Big Five personality (β = 0.626; p < 0.01) and cross-cultural adaptation (β = 0.287; p < 0.05). Big Five personality also contributed strongly to cross-cultural adaptation (β = 0.489; p < 0.001), with an R² value of 0.818 for adaptation. Conversely, acculturation strategies were not proven to have a direct effect on personality or adaptation. These findings confirm that interpersonal communication plays a key role in bridging the influence of personality on successful cultural adaptation. Theoretically, this study expands the integration of the Big Five Personality Traits with the Berry Acculturation Model in the context of domestic migrant students in Indonesia, a relatively understudied area. Practically, the results encourage universities to strengthen communication soft skills development programs and provide multicultural interaction spaces to support student adaptation.